IMPLEMENTASI 7 KEBIASAAN ANAK INDONESIA HEBAT DALAM PEMBENTUKAN KARAKTER ANAK - Purwanti, Camelia Istiqomah; Sanjaya, Dewa Bagus; Suastika, I Nengah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the implementation of the 7 Habits of Great Indonesian Children program in character building for children. Character education is considered a major pillar in creating a quality young generation, and the Indonesian government has issued policies to strengthen it through this program. However, the results of the study indicate that there are challenges faced by children in adopting positive habits such as waking up early, exercising, eating healthily, and being fond of learning. Therefore, parent training and habituation programs in schools are needed to increase the effectiveness of these habits. The Islamic perspective on character education is also in line with this program, which aims to form a generation that is faithful, pious, and has noble morals. Synergy between parents, teachers, and the surrounding environment is a key factor in forming consistent good habits. In addition, the digital era brings new challenges in character building, but the implementation of 7 Habits of Great Indonesian Children has been proven to improve student discipline, both in time management and social and academic discipline. Active support from teachers and parents is very important in overcoming the challenges that arise. This study concludes that the successful implementation of this program requires continuous evaluation and mentoring as well as the involvement of all related parties.